2016
DOI: 10.1063/1.4948442
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of low-level laser irradiation on umbilical cord mesenchymal stem cells

Abstract: Low-level laser irradiation (LLLI) can enhance stem cell (SC) activity by increasing migration and proliferation. This study investigated the effects of LLLI on proliferation, enzymatic activity, and growth factor production in human umbilical cord mesenchymal SCs (hUC-MSCs) as well as the underlying mechanisms. hUC-MSCs were assigned to a control group (non-irradiation group) and three LLLI treatment groups (635 nm group, 808 nm group, and 635/808 nm group). Laser power density and energy density of 20 mW/cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…LLLT at 4 J/cm 2 partially reversed the activation of DNA oxidation, caspase 3/8, IL-1β/6 and IFN-γ induced by H 2 O 2 , with an increased level of anti-inflammatory IL-10. Similar to the findings by Fernandes on M1 macrophage, a report by Chen et al on human umbilical cord mesenchymal stem cells found that LLLT (635 nm, 808 nm, 635 + 808 nm, 12 J/cm 2 , two daily treatments for 3 days) promoted the expressions of proinflammatory cytokines IL-1, IL-6 along with NF-κB (41), but this was also accompanied by an increase in cell proliferation.…”
Section: Apoptosissupporting
confidence: 79%
“…LLLT at 4 J/cm 2 partially reversed the activation of DNA oxidation, caspase 3/8, IL-1β/6 and IFN-γ induced by H 2 O 2 , with an increased level of anti-inflammatory IL-10. Similar to the findings by Fernandes on M1 macrophage, a report by Chen et al on human umbilical cord mesenchymal stem cells found that LLLT (635 nm, 808 nm, 635 + 808 nm, 12 J/cm 2 , two daily treatments for 3 days) promoted the expressions of proinflammatory cytokines IL-1, IL-6 along with NF-κB (41), but this was also accompanied by an increase in cell proliferation.…”
Section: Apoptosissupporting
confidence: 79%
“…25 A laser with a wavelength of 635nm amplified the umbilical cord mesenchymal cells if it proved that a low-power laser with 808nm failed to increase the proliferation of the same cells. 26 Adipose Mesenchymal Stem Cells It has been reported that the toxic effects of doxorubicin on the adipose mesenchymal stem cells can be reduced by using a low-power laser with a wavelength of 660 nm, output power of 30 mW, a laser beam of 0.028 cm 2 , and irradiation of 1.07 mW/cm 2 . A Low-power laser with these features increases the viability of the MSCs and inhibits apoptosis and oxidative stress in the MSCs that are treated with doxorubicin.…”
Section: The Variety Of Mesenchymal Stem Cells Umbilical Cord-mesenchmentioning
confidence: 99%
“…12 Later in another work, they used 635 nm and 808 nm laser irradiation on stem cells. 21 They used these wavelengths separately and also as dual-wavelength laser and they concluded using both wavelengths on one sample could be more effective. 21 In another study, Unnikrishna Pillai and Padma used laser irradiations with wavelengths 476 nm, 488 nm, and 514 nm on seeds, and concluded that, the 476 nm wavelength had more effect on increasing the activity of catalase.…”
Section: Introductionmentioning
confidence: 99%
“…21 They used these wavelengths separately and also as dual-wavelength laser and they concluded using both wavelengths on one sample could be more effective. 21 In another study, Unnikrishna Pillai and Padma used laser irradiations with wavelengths 476 nm, 488 nm, and 514 nm on seeds, and concluded that, the 476 nm wavelength had more effect on increasing the activity of catalase. 22 Many different studies were conducted to investigate the effect of laser irradiation on parotid glands in diabetes rats.…”
Section: Introductionmentioning
confidence: 99%